2000
DOI: 10.1046/j.1469-8137.2000.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Does calcium ameliorate the negative effect of NaCl on melon root water transport by regulating aquaporin activity?

Abstract: The hydraulic conductance (L ! ) of detached, exuding root systems from melon (Cucumis melo cv. Amarillo oro) was measured. All plants received a half-strength Hoagland nutrient solution, and plants stressed either solely with NaCl (50 mM) or with NaCl (50 mM) following treatment (2 d) with CaCl # (10 mM) were compared with controls and CaCl # -treated (10 mM) plants. The L ! of NaCl-treated plants was markedly decreased when compared to control and CaCl # -treated plants, but the decrease was smaller w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(64 citation statements)
references
References 50 publications
6
55
0
3
Order By: Relevance
“…Okadaic acid and vanadate are commonly used as inhibitors of protein phosphorylation (Cohen and Cohen, 1989;Gordon, 1991). We have also demonstrated that the calcium channel blocker, 1 mM LaCl 3 , significantly inhibited L p at 25°C, further supporting the notion that aquaporin gating is linked to the calcium signal (Johansson et al, 1996;Carvajal et al, 2000;Németh-Cahalan and Hall, 2000;Azad et al, 2004).…”
Section: Discussionsupporting
confidence: 76%
“…Okadaic acid and vanadate are commonly used as inhibitors of protein phosphorylation (Cohen and Cohen, 1989;Gordon, 1991). We have also demonstrated that the calcium channel blocker, 1 mM LaCl 3 , significantly inhibited L p at 25°C, further supporting the notion that aquaporin gating is linked to the calcium signal (Johansson et al, 1996;Carvajal et al, 2000;Németh-Cahalan and Hall, 2000;Azad et al, 2004).…”
Section: Discussionsupporting
confidence: 76%
“…Exogenous ALA application remarkably reduced the damage caused by salinity stress and improved plant biomass accumulation in both tomato cultivars, which is consistent with previous research on cotton (Watanabe et al, 2000) and potato (Zhang et al, 2006). Salinity stress decreases osmotic pressure dependent hydraulic conductance in melon roots (Carvajal et al, 2000). Likewise, root hydraulic conductance and E in citrus were remarkably reduced by long-term salt treatments (Rodriguez-Gamir et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…In ice plants, transcript levels of some aquaporins are down-regulated in the first 30 h after exposure to salt stress and recover when this stress is interrupted (Yamada et al, 1995). Likewise, NaCl reduces either the activity or abundance of Hg-sensitive water channels (aquaporins) as shown by measuring the osmotic pressuredependent hydraulic conductivity of detached, exuding root systems from paprika pepper (Carvajal et al, 1999) and from melon (Carvajal et al, 2000). In line with these observations, the amount of LeTIP and LePIP1 but not of LePIP2 transcripts was found to be down-regulated by roughly 20% under continuous salt stress in the present communication (Fig.…”
Section: Discussionmentioning
confidence: 99%